Transpor Ion Logam Cu(II) Menggunakan Minyak Kelapa (Cocos nucifera L.) Sebagai Membran Cair Melalui Teknik Membran Cair Fasa Ruah - Refinel; Olly Norita, Tetra; Shofiyah , Anwar (Departemen Kimia Universitas Andalas, 2024)
Increasing industrial activities throughout the world produce a large amount of waste, including materials that contain heavy metal ions. One of the heavy metals found in industrial waste is copper ion Cu(II). Liquid membrane technology using vegetable oil as the membrane phase can be an environmentally friendly alternative metal transportation process. Transport of Cu(II) ions was carried out using bulk li-quid membrane technology using coconut oil as the phase membrane. According to the Minister of Health Regulation No. 492/menkes/per/IV/2010 concerning Drinking Water Quality Requirements, the threshold limit of Cu(II) ions in waters is 2 mg/L. Many ways have been done to separate heavy metal ions from this industrial waste. In this study, the transport of Cu(II) ions through coconut oil membrane and as the receiving phase of ethylenediaminetetraacetic (EDTA) has been carried out. The optimization results obtained, namely the source phase of Cu(II) metal ions pH 4 with a concentration of 3.147 x 10-4 M, the receiving phase of EDTA solution pH 7 with a concentration of 0.06 M, 200 rpm stirring speed, obtained the transport of Cu(II) metal ions to the receiving phase, namely, 23.44% with a transport time of 1 hour. Furthermore, the test was carried out with the same optimum conditions using HCl as the receiving phase, and the percentage value of Cu(II) metal ions in the receiving phase was 25%, from using the EDTA receiving phase.